2022
DOI: 10.18280/ts.390617
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to Single-Channel Fetal Electrocardiogram Identification

Abstract: This paper presents the recognition of fetal ECG signals from a single-channel recording. The Continuous Wavelet Transform generates a two-dimensional representation of a single-dimension input containing fetal electrocardiogram waves, which are accurately located and isolated. By segmenting this 2D representation using Otsu's method, the continuous wavelet transform of each wave may be estimated. The temporal expression of the wave is then rebuilt by calculating the Inverse Continuous Wavelet Transform. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These initial results demonstrate promising performance, providing a solid foundation for further analysis and improvement through regularization techniques. By comparing the obtained results with recent works in the field, as demonstrated in references [6,7,8,9], it can be concluded that the achieved results are optimal. These results surpass the performance reported in the referenced studies, indicating a significant improvement in the signal separation process.…”
Section: Ecg Recordingmentioning
confidence: 53%
“…These initial results demonstrate promising performance, providing a solid foundation for further analysis and improvement through regularization techniques. By comparing the obtained results with recent works in the field, as demonstrated in references [6,7,8,9], it can be concluded that the achieved results are optimal. These results surpass the performance reported in the referenced studies, indicating a significant improvement in the signal separation process.…”
Section: Ecg Recordingmentioning
confidence: 53%